Visible light mediated, metal and oxidant free highly efficient cross dehydrogenative coupling (CDC) reaction between quinoxalin-2(1H)-ones and ethers - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (New Journal of Chemistry, 2019)
The efficient and metal free, white light mediated 3C alkylation of quinoxalin-2(1H)-ones via a cross dehydrogenative coupling reaction with cyclic ethers using eosin Y as a photocatalyst is described. This reaction has broad substrate scope and strong functional group tolerance with good to excellent yields.